Core Employability Skills dan Kompetensi Teknik Siswa SMK Menghadapi Persaingan Global - Dedi Sutrisna; Dede Abdul Rozak (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2023)
The threat of entry of foreign workers into Indonesia has increasingly narrowed employment opportunities in Indonesia. This also has an impact on the Vocational High School (SMK) as an educational institution that produces middle-level skilled workers, so this institution is required to always improve the quality of its graduates according to the standards needed by the business and industrial world which continue to develop along with globalization. On the other hand, data from the Central Statistics Agency (BPS) shows that there is still a high unemployment rate for SMK graduates, which indicates that SMK graduates lack competitiveness in the business/industry world. This study aims to describe Job Readiness as measured by Core Employability Skills (CES) and Technical Competency. (KT) students of Building Skills Vocational School facing global competition in Ciamis Regency. The combination method was used on a sample of 172 students of Class XII Vocational High School Building Engineering Competency in Ciamis Regency, with the instrument scores, questionnaires, interviews, observations, and documentation. From the results of the study, it was found that CES and KT for vocational students facing global competition, seen from the curriculum, ACSF, and SKKNI targets, they reached the competent category.